ANALISIS FAKTOR-FAKTOR PERSEPSI PEGAWAI MENGENAI PENGGELAPAN PAJAK (STUDI KASUS PADA BALAI PEMERINTAHAN DESA DI DIY) - Maulidya Ikhbar Nurfaizah; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to analyze and get empirical evidence on employee perceptionsabout the government of the special region of Yogyakarta Village regarding theeffect of the taxation system, protection against tax incorporation. This researchis a quantitative study and the population is all employees who are within thescope of the Yogyakarta Special Region Government Village. For sample selectionis to use a saturated sample that obtained as many as 86 respondents to bestudied. In collecting data using a questionnaire method and for data analysisusing the SPSS program. The results of this study indicate that the variables ofjustice and discrimination affect tax evasion. The taxation system variable hasno effect on tax evasion.